Nonintervention and International Order - Vincent, R. J. (Book collections on Project MUSE., 2015)
Frequent instances of intervention in current world affairs have threatened the status of nonintervention as a rule of international relations. Gathering evidence from history, law, sociology, and political science, R.J. Vincent concludes that the principle of nonintervention can and must remain viable. The author approaches the question from several angles, seeking to discover why the principle of nonintervention has been asserted as part of the law of nations; whether states in the past and present have conducted their foreign relations according to the principle of nonintervention; and w.